The Influence of Work Discipline, Incentives and Teamwork on Employee Performance at BAZNAS Surabaya City - Fitria Bella Kusuma Wardani; M. Sihab Ridwan (Asian Journal of Applied Business and Management, 2023)
This research aims to determine the partial or simultaneous influence of the independent variables Work Discipline, Incentives and Teamwork on the dependent variable Employee Performance at BAZNAS Surabaya City. This research uses quantitative methods. The data collection technique in this study was a survey technique with a questionnaire as an instrument. Data analysis in this research uses validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and the coefficient of determination (R2), while hypothesis testing techniques use the t test and F test. Work Discipline partially has a significant positive effect on Employee performance; incentives partially have a significant positive effect on employee performance; and teamwork partially has a significant positive effect on Employee performance. Simultaneously, work discipline, incentives, and Teamwork have a significant effect on Employee Performance.